On the Use of Bonus Payments in an Experimental Study of Electricity Demand - Fishe, Raymond P. H.; McAfee, R. Preston (The Review of Economics and Statistics, 1983)
Results of an analysis show that the use of bonus payments in an experimental study of electricity demand is directly related to the income effects in the Slutsky equation. As with the income effect, it is not possible to predetermine the sign of the bonus effect. Theoretical results predict that if the relationship between the bonus payment and consumption of electricity is severed, then households would unambiguously increase consumption. The authors conclude that bonus plans will reduce electricity consumption and could be an alternative approach to promoting conservation. 10 references, 1 table.